The principle of accounting disclosure and its role in tax accounting (Applied research in the General Tax Authority in Iraq) - Faisal Sarhan Aboud; Saleh Mahdi Hamadi (The Scientific Journal of Cihan University– Sulaimaniya, 2017)
The research discussed the determination basic requirements in principle of accounting disclosure in the financial reports and measurement the level of commitment the contribution company (research sample) with it’s requirements and clarification the important of principle of accounting disclosure and it’s role in reengineering on procedure of tax to arrive to the results of and objective accurate examination achievement desired justice in calculation of taxable income.